DRIMM: DRINK MIXING MACHINE UNTUK MEMBANTU PEDAGANG MINUMAN MENENTUKAN TAKARAN AIR YANG KONSISTEN - Muhammad Adam Nahdlotul Halimi; Mohamad Nurkamal Fauzan; Roni Habibi; Noviana Riza (Universitas Widyatama, 2019)
Abstract Electrolyte is one of the fluids in the human body. This electrolyte is used to maintain fluid balance in the body. Lack of electrolytes can lead to dehydration. Dehydration can be overcome by drinking drinks that contain electrolytes. However, the drinks sold by traders do not necessarily contain electrolytes that are safe for consumption by the human body. So a machine to help traders to make drinks with safe electrolyte content is necessary. From these problems, the authors have made a machine for mixing drinks. This tool is named DRIMM (Drink Mixing Machine). DRIMM will provide a mixture of drinking water with a dose that has been processed using the Multiple Linear Regression method. From the results of experiments conducted, the tool can make a mixture of water with an average electrolyte concentration of 654 PPM. So that the electrolyte content in the drink is in accordance with a safe dose for consumption by the body. With this tool, it is expected to help traders in the process of making their drinks. The trader as well as the customers will no longer worry about the electrolyte content in their drinks. Keywords: Electrolytes, Arduino, Microcontroller, Mixing, Multiple Linear Regression